Kontribusi Pupuk Organik Kotoran Sapi Terhadap Tinggi Tanaman Padi (Oryza sativa L.) - Syahfitri, Aulia Insyani; Anhar, Azwir; Violita, Violita; Kardiman, Reki (Jurnal Serambi Biologi, 2024)
Continuous use of inorganic fertilizers on rice plants has a negative impact on soil productivity and the environment so that plant growth is disrupted. Therefore, it can be used to reduce the impact of using inorganic fertilizers by using organic fertilizers. This research aims to determine the effect of the composition of organic cow dung fertilizer and inorganic fertilizer on the growth of rice plants which was carried out from July to November 2023 at the Plant Physiology and Wire House Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Padang State University. This research was structured using a Completely Randomized Design (CRD) consisting of 6 treatments and 4 replications. The treatment given consisted of A = 100% NPK Fertilizer + 0% Cow Manure, B = 80% NPK Fertilizer + 20% Cow Manure, C = 60% NPK Fertilizer + 40% Cow Manure, D = 40% NPK Fertilizer + 60% Cow Manure Fertilizer, E = 20% NPK Fertilizer + 80% Cow Manure Fertilizer, F = 0% NPK Fertilizer + 100% Cow Manure Fertilizer. The results showed that the influence of the composition of inorganic NPK fertilizer and organic cow dung fertilizer for rice plants had no significant effect on plant height at 15, 30, 45 and 60 HST.